The Flight of the Postmodern Fly: Sociology and Post-Positivistic Analytics of Richard Rorty - Šaulauskas, Marius Povilas (Sociologija. Mintis ir veiksmas, 1997)
While Richard Rorty cannot be considered a ‘real’ sociologist, he provides a significant contribution the methodology of the social sciences. Rorty’s critical pragmatism is an important component of postmodern sociology. Always critical and sometimes even too flaunty about its novelty, postmodern mindset develops within labyrinths of interdisciplinary matter. In such a confusing polyphonic and conceptually mixed surrounding common theoretical contrapositions, provisions and concepts soften their strictness. Postmodern social criticism, which sooner or later undergoes the necessity to speak not only denying but also to use the stating voice, must ask: if there is nothing truthful to be said, why is it needed and, if yes, how is it possible not to lose voice?
Keywords: postmodernity; sociology; critical pragmatism; Richard Rorty